APLIKASI PELAPORAN DATA GAINT AND LOSSES SPBU 23.361.03 KOTA JAMBI BERBASIS WEB - Ikhsan, Muhammad; Adhiatma, Novri; Sauri, Muhammad (FORTECH (Journal of Information Technology), 2020)
The gaint and losses data reporting system at SPBU 23.361.03 Jambi City that is running is already computerized using Microsoft Excel but its use is not maximized so that a problem arises in terms of the effectiveness and efficiency of fuel depreciation data reporting becomes an information in the management process at SPBU 23.361.03.In connection with the problems mentioned above, the researcher tries to design a depreciation data reporting system to facilitate the administration in the process of reporting shrinkage data. From the process of analyzing and developing the system, this data reporting system can make it easier for relevant agencies to search for data and check transaction data and also administration conducted by SPBU 23.361.03 Jambi City.